PEMBERDAYAAN DAN PENINGKATAN DAYA SAING INDUSTRI KERUPUK TRADISIONAL PADA USAHA RUMAHAN DI SURABAYA - Irawati, Desrina Yusi; Purba, Lasman Parulian; Canariesa, Armadeo Ruben; Massa, Paschal Nicollas Dominggo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The cracker industry is an important part of Surabaya’s traditional culinary heritage and is largely operated by micro-scale enterprises with simple management systems. One such enterprise is the cracker business owned by Mrs. Ponining in East Surabaya. This business faces several challenges, including non-standardized production processes, inconsistent quality control, unsystematic financial record-keeping, and product packaging without a clear brand identity. This community service program aims to enhance the capacity of Mrs. Ponining’s cracker business through assistance in production, business management, and marketing. The interventions include the implementation of simple production standard operating procedures (SOPs), the application of 5S principles to improve workplace organization and hygiene, mentoring in simple yet systematic financial record-keeping, and the development of product packaging and labeling as business identity. Several constraints were encountered during implementation, such as limited time availability and the persistence of traditional business practices. However, these challenges were addressed through gradual mentoring and hands-on assistance tailored to the conditions of micro-scale enterprises. The results indicate improvements in product quality consistency, production efficiency, financial management orderliness, and product packaging. This program is expected to support the sustainability of the cracker business and serve as a model for empowering traditional micro-scale food enterprises in urban areas.